Fabrikasi dan Karakterisasi Sensor Elektrokimia untuk Mendeteksi Kadmium Berbasis Teknologi Film Tebal - Riska Sri Wahyuni; Robert V. M.; Arifin Arifin (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2020)
Electrochemical sensor has been fabrication and characterization electrode to detect heavy metals of cadmium with thick film technology. Fabrication electrodes electrochemical sensors start with the design stage of electrodes, screen maker, screen printing, and substrate cutting. The fabrication process produces a ten-pieces of sensors to be used to sensors characterization of SEM, XRD, and Cyclic Voltammetry (CV). The process of characterization produces morphology and the structure of the composites N/IL/G, and linieritas 0,9623, precision ranges between 4,11 and 10,35%, sensitivity of 0,04112 µA.L-1/mg.mm2, limit detection 0,18 mg/L, and accuracy between 79,5 and 126,8%.